Simulator för el- och värmeproduktion : påverkan på ekonomi och miljö - Hellström, Erik; Hermansson, David (SLU/Dept. of Energy and Technology, 2013)
In this project a simulator has been developed (in C++) with the purpose of illustrating how changes in environmental regulations, tax levels and other policy measures affect the composition of an energy system. The aim of the project was to investigate how energy companies’ investment strategies are affected when changes in economic and environmental conditions occur. A standard scenario has been created based on current Swedish conditions, but the user can create new scenarios and set parameters freely. The user is tasked with building power plants to supply the city/region with district heating and electricity during a pre-set number of years. When the simulation is finished the result is graded in the following categories: economy, environment and quality.